FDG‐PET metabolic tumor parameters for the reirradiation of recurrent head and neck cancer. (24th March 2018) - Velez, Maria A.; Veruttipong, Darlene; Wang, Pin‐Chieh; Abemayor, Elliot; St. John, Maie; TenNapel, Mindi; Chen, Allen M.
Abstract : Objective: The utility of fluorodeoxyglucose positron emission tomography (FDG‐PET) imaging to predict outcome has been well‐established for patients undergoing definitive radiation in the initial management of head and neck cancer. However, the usefulness of this modality in the recurrent setting remains uncertain. We sought to evaluate the prognostic value of metabolic tumor parameters measured on FDG‐PET in patients treated by reirradiation for recurrent head and neck cancer. Methods: Thirty‐four tumors occurring in 29 patients were reirradiated and were evaluable. The most common disease sites were the oropharynx (n = 9), oral cavity (N = 8), and nasopharynx (n = 6). Potential correlations of FDG‐PET maximum standardized uptake value (SUV) and metabolic tumor volume (MTV) with survival endpoints were explored. Multivariate analysis was performed using Cox proportional hazard. Results: The median MTV, SUV, and gross tumor volume, as delineated using the 50% SUVmax threshold, were 366 cc (range, 0–3, 567 cc), 8.1 (range, 0–25), and 48.5 cc (range, 1–190 cc), respectively. On univariate analysis, both MTVs (as measured as a continuous variable and using the median value of 266 cc as cutoff) were predictive of decreased overall survival ( P < 0.05 for both). A strong trend toward decreased progression‐free survival ( P = 0.05), in‐field control ( P = 0.06), and locoregional control ( P = 0.07) was also observed with increasing MTV when analyzed as a continuous variable. Multi‐variate analysis confirmed MTV as an independent predictor of mortality. Conclusion: The PET‐derived parameter MTV may serve as a potentially valuable factor for risk stratification and for guiding treatment in future reirradiation trials. Level of Evidence: 4. Laryngoscope, 128:2345–2350, 2018